CORPORATE SOCIAL RESPONCIBILITY (CSR) PELINDO II TANJUNG PRIOK JAKARTA UTARA SEBAGAI BENTUK PEMBANGUNAN YANG BERKELANJUTAN (Studi Kasus di Tanjung Priok di Kecamatan Koja dan Lagoa Jakarta Utara) - Rurry Andryanda Rurry Andryanda (LPPM STIA Banten, 2016)
The purpose of this paper is to analyze the social responsibility programs implemented by Pelindo II Tanjung Priok in Koja sub- istrict and Lagoa. The problem often faced by their firm rejection by the people in the surrounding area of the company. Their CSR program will help empower the people so that the welfare of society for the better. The activities planned by the company generally involve the community and the government. In order to maintain the existence of the company, then the company should be able to maintain a balance between the desire of companies to the understanding of the community. The way to do is look at the potential social, economic, cultural and security around the company.